TEKS PESANTREN TENTANG PENDIDIKAN KEBANGSAAN - Said Aqil Siradj (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
Â Scientific texts of pesantren cannot be separated from the treasure of Yellow Books of pesantrens written by Islam scholars from 3n century to 10th century of Hijnjyah. Yellow Books are primag references of the majority, if not all, of pesantren communities to solve any humanity problems with ubudiyah (worship) muamalat (social interaction), munakahat (marriage), siyasah (strategy), etc. Through these Yellow Books pesantrens produce tasamuh, tawaZun and Ptidal attitudes. Related to the nationality problem recently discussed everywhere, in . term of doctrinism, pesantrens have long developed what a so-called principle of ukhuwah wathoniyah (nationality brotherhood). This article points out how pesantrens, through their education in form of moral cultivation, have proved themselves as being capable of keeping children from moral erosion and decadence. It will save the nationÂ from social diseases such as corruption, collusion, and so on.